2013
DOI: 10.1111/joor.12097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interocclusal distance on bite force and masseter EMG in healthy participants

Abstract: The aim of this study was to investigate effects of interocclusal distance (IOD) on bite force and masseter electromyographic (EMG) activity during different isometric contraction tasks. Thirty-one healthy participants (14 women and 17 men, 21·2 ± 1·8 years) were recruited. Maximal Voluntary Occlusal Bite Force (MVOBF) between the first molars and masseter EMG activity during all the isometric-biting tasks were measured. The participants were asked to bite at submaximal levels of 20%, 40%, 60% and 80% MVOBF wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 57 publications
3
23
1
1
Order By: Relevance
“…The significance of this movement lies in its relation to the bite force. Studies showed that maximum bite force tends to vary when measured at different jaw openings . Rosentritt et al reported that increasing the mouth opening distance from 2 to 4 mm caused only superficial changes in the specimens with small influence on the post‐fatigue fracture resistance …”
Section: Discussionmentioning
confidence: 99%
“…The significance of this movement lies in its relation to the bite force. Studies showed that maximum bite force tends to vary when measured at different jaw openings . Rosentritt et al reported that increasing the mouth opening distance from 2 to 4 mm caused only superficial changes in the specimens with small influence on the post‐fatigue fracture resistance …”
Section: Discussionmentioning
confidence: 99%
“…To keep the mandible balanced, the other pre‐molar side (the balancing side) was clenching a 10‐mm‐diameter cotton roll. The TMD subjects were preferentially using their asymptomatic muscles , whereas healthy participants showed higher masseter muscles EMG activity in the dominant side . Bite force was displayed on the computer screen as visual feedback to the subject, allowing the subject to know their bite force values.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Roldan et al showed that the molar bite force was higher than the incisor bite force (15). A previous study by Arima et al showed that the MVOBF decreased with increased interocclusal distance between 8 mm to 12 mm (18). This difference may be caused by differences in the interocclusal distance.…”
Section: Maximal Voluntary Occlusal Bite Force Levelsmentioning
confidence: 98%